Masked Warrior with Daggar - G.F. MacDonald Collection (1979)
Victor Mowat in the re-enactment of the Epic of Nekt at 'Ksan, directed by G.MacDonald. The story takes place at 'Battle Hill near Gitwangak village. 'Nekt was an aggressive warrior and led many successful raids against neighbouring tribes. He is remembered and celebrated by the Gitxsan people as a powerful and great leader.